Objectivity in Muslim Scholars’ Studies of Religions: Abu Al-Hasan Al-Amiri as an Example - Chetioui, Soufiane (Journal of Islamic and Religious Studies, 2025)
The research is based on the idea that the cognitive content of objectivity is present in Al-Amiri’s writings about religions, as they are among the Islamic sources founding the science of comparative religion. It aims to highlight the features of objectivity according to Al-Amiri, through a set of methodological elements that he employed in his study. The research is divided into three main sections. The first was devoted to controlling the concept of objectivity and proving its specificity in Islamic thought. The second was devoted to introducing Abu al-Hasan al-Amiri and his writings on religions. The third was devoted to highlighting the features of his objectivity in the study of religions. The research concludes with a number of results, the most important of which are: Al-Amiri’s awareness of the “idea” of objectivity, its presence in his mind, and his commitment to its conditions and terms in his study, which confirms the primacy of the Islamic sources founding the science of comparative religion in adhering to the controls of scientific research.